Organic matter fractions and N mineralization in vegetable‐cropped sandy soils. (18th March 2013) - Jegajeevagan, K.; Sleutel, S.; Ameloot, N.; Kader, M. A.; De Neve, S.
Abstract: Soil organic nitrogen mineralization rates and possible predictors thereof were investigated for vegetable‐growing soils in Belgium. Soil organic matter (SOM) was fractionated into sand (> 53 μm) and silt+clay (< 53 μm) fractions. The latter fraction was further separated into 6%NaOCl‐oxidation labile (6%NaOCl‐ox) and resistant N and C and subsequently into 10%HF‐extractable (mineral bound) and resistant (recalcitrant) N and C. The N mineralization turnover rate (% of soil N/year) correlated with several of the investigated N or C fractions and stepwise linear regression confirmed that the 6%NaOCl‐ox N was the best predictor. However, the small R² (0.42) of the regression model suggests that soil parameters other than the soil fractions isolated here would be required to explain the significant residual variation in N mineralization rate. A next step could be to look for alternative SOM fractionations capable of isolating bioavailable N. However, it would appear that the observed relationships between N fractions and N mineralization may not be causal but indirect. The number of vegetable crops per rotation did not influence N mineralization, but it did influence 6%NaOCl‐ox N, probably as an effect of differences in crop residues returned and organic manure supply. However, the nature of this relation between management, SOM quality and N mineralization is not clear. Explanation of correlations between N mineralization and presumed bioavailable N fractions, like the 6%NaOCl‐ox N, requires further mechanistic elucidation of the N mineralization process.